REPS-AKA5: A robust group-based authentication protocol for IoT applications in LTE system - Mobarhan, Mostafa Ayoubi; Salamah, Muhammed (Elsevier, 2023)
Nowadays, Internet of Things systems connect several smart devices to provide required services. The IoT applications employ Machine Type Communications to meet the requirements of IoT applications. In such systems, one of the most important challenges is providing a proper security level for each IoT device. The LTE network is an appropriate network for IoT systems. One of the most important objectives in an LTE-enabled IoT network is to manage a great number of IoT devices with a high level of security. In addition, when plenty of IoT devices connect to the LTE system simultaneously, all the IoT devices need to run a full AKA process, which might make problematic signaling congestion. Thus, supporting a huge number of IoT nodes (i.e., devices) is a fundamental requirement of IoT systems. In this paper, taking into consideration the important performance and security issues, we suggest a lightweight group-based AKA protocol for IoT applications called Robust Evolved Packet System-Authentication and Key Agreement 5 (REPSAKA5) protocol. The proposed method presents a strong mutual authentication between all involved nodes. In addition, the suggested approach presents considerable confidentiality in the data/control plan using an optimized combination of symmetric and asymmetric keys. By the proposed method, a huge number of IoT devices can be simultaneously verified by the LTE system. We verified the proposed AKA method by using the AVISPA tool and BAN logic, Scyther tool to check that the REPS-AKA5 method is resistant to different known security attacks. Furthermore, the obtained results show that the proposed method provides better performance compared with other AKA methods in terms of computational cost, storage overhead, bandwidth consumption, and signaling overhead. Hence, the REPS-AKA5 approach is able to achieve not only defined security requirements but also a considerable improvement in network performance.
Keywords: M2M communication; LTE Security; AVISPA tool; BAN logic; Scyther verification tool; Group-based authentication and IoT systems